Dreamgirls [videorecording (DVD)] - Krieger, Henry (DreamWorks Home Entertainment, 2006)
Three young women, Deena Jones, Effie White and Lorrell Robinson desire to become pop stars. They get their wish when they are picked to be backup singers for the legendary James "Thunder" Early. When they are set free for leads, Curtis Taylor and Effie's brother C.C. decide that Deena should be the lead singer, which upsets Effie. The girls discover exactly what it takes to be in the music business and what they must give up to realize their dreams.